A Randomized Controlled Trial of Transcultural Validation of Group-Based Psychosocial Intervention for Patients with Bipolar Disorder. (August 2020) - Lin, Chen-Ju; Huang, Yu-Hsin; Huang, Kuo-Yang; Wu, Shu-I; Chang, Yi-Hung; Yeh, Hsiao-Mei; Chang, Chih-Hung; Lin, I-Chieh; Huang, Hui-Chun; Sun, Fang-Ju; Berk, Michael; Liu, Shen-Ing
Highlights: Examining efficacy of group psychosocial intervention in Chinese BD outpatients. The model helped achieve euthymia, reduce depressive symptoms, and improve QoL. Medication adherence, manic symptoms control, and suicidal ideation did not improve. ABSTRACT: Adjunctive psychosocial interventions are part of the preferred method to treat bipolar disorder (BD). This study aimed to conduct a randomized control and protocol-guided trial, in order to evaluate the feasibility and effectiveness of adjunctive group-based treatments for Chinese outpatients with BD. A single-blind trial in which 68 outpatients with BD were randomly assigned to either treatment as usual (TAU) or to an experimental group with 12 additional weekly sessions and 3 monthly booster sessions. Participants were assessed at baseline for mood condition, suicidal ideation, medication adherence, and quality of life (QoL), with follow-up assessments every 3 months over a 1-year period. The overall retention rate of this study was 89.7%. The results showed significant differences between groups for the variables evaluated, which included achieving euthymia, decrease of depression symptoms, and improvement of QoL. No improvements in medication adherence, reduction in manic symptoms, or suicidal ideation was observed. The results of this study support the transcultural validity and efficacy of group-based psychosocial intervention as anadjunct to TAU among Chinese outpatients with BD to promote improvements during the course of the illness including achieving euthymia, reducing depressive symptoms, and improving QoL.